Pied-pipers wanted: The search for super-lures of New Zealand mammal pests - Linklater, Wayne; Greenwood, David; Keyzers, Robert; Duckworth, Janine; Banks, Peter; MacKay, Jamie; Stockum, Christine (New Zealand Science Review, 2013)
​Introduced mammalian competitors and predators are the leading threat to New Zealand’s native wildlife (Craig et al. 2000). The recent Pest Summit (3–4 December, 2012: Linklater 2013a) identified improving ways of detecting and killing mammals as the top three research priorities. One of these was the development of better lures to attract pest mammals to monitoring and killing devices. We have fought conservation battles largely with existing food-based lures. Mammals have been eradicated on islands and their populations depressed on the mainland. But we are not yet winning the war. Eradication of the worst mammal pests remains improbable on the mainland because current technolo-gies cannot operate at the required scale and intensity within probable budgets. The extensive deployment of killing devices for extermination at greater scales is juxtaposed logistically against the intensity of effort required to kill the few last, most difficult to detect, animals.